2016
DOI: 10.1002/open.201600136
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Investigation of Adsorption of Single-Wall Carbon Nanotubes at a Liquid/Liquid Interface

Abstract: There is much interest in understanding the interfacial properties of carbon nanotubes, particularly at water/oil interfaces. Here, the adsorption of single‐wall carbon nanotubes (SWCNTs) at the water/1,2‐dichloroethane (DCE) interface, and the subsequent investigation of the influence of the adsorbed nanotube layer on interfacial ion transfer, is studied by using the voltammetric transfer of tetramethylammonium (TMA+) and hexafluorophosphate (PF6 −) as probe ions. The presence of the interfacial SWCNT layer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Set against the blocking effect of the film, the modest current enhancement indicates that the presence of MoS 2 nanosheets at the interface could lead to a net increase in its roughness, which leads to an increase in interfacial area. However, other studies on nanomaterials reported either unaltered or lower peak current responses upon introducing nanomaterials at the interface, e. g. carbon nanotubes [25] and gold nanoparticles [22] . Thus, even though the presence of nanomaterials at the interface increases the total interfacial area, its effect is not necessarily enough to induce a significant increase in the peak current.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Set against the blocking effect of the film, the modest current enhancement indicates that the presence of MoS 2 nanosheets at the interface could lead to a net increase in its roughness, which leads to an increase in interfacial area. However, other studies on nanomaterials reported either unaltered or lower peak current responses upon introducing nanomaterials at the interface, e. g. carbon nanotubes [25] and gold nanoparticles [22] . Thus, even though the presence of nanomaterials at the interface increases the total interfacial area, its effect is not necessarily enough to induce a significant increase in the peak current.…”
Section: Resultsmentioning
confidence: 93%
“…While this structure, which involves radial diffusion together with a larger interfacial area, is thought to enhance the ion transfer processes across the interface, it may not exclusively generate an enhancement to the peak current. Interfacial emulsions were also reported for adsorbed carbon nanotubes at the interface, yet the ion transfer across the interface was not enhanced [25] . Thus, the significant enhancement to the mass transport may also involve an interaction between the transferring ions with the adsorbed material.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A broadening of the electrolyte ion transfer limiting the potential window is also seen in the presence of CNTs, indicating that their presence inhibits this process at the interface. 55 For PB electrodeposition at the L/L interface, 6 ] was added to the aqueous phase. Due to the narrower useful potential window when compared with the 3-electrode system, lower pHs were tested for the modification of CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…Hopefully, the concept of utilizing biphasic reaction within fuel cell/ electrolyzer for hydrogen peroxide generation [110] will be realized with heterogeneous catalyst assembled at the liquid j liquid interface. In this context, better understanding of ion transfer across liquid j liquid interface modified with nanoobject assembly [140,141] is desirable. So far, almost all studies of biphasic HER, OER and ORR focused on quiescent system with two bulk phases are in direct contact and interfacial area is restricted by the size and shape of the cell.…”
Section: Discussionmentioning
confidence: 99%